REDUCING POSTHARVEST LOSSES IN NIGERIA’S AGRICULTURAL SECTOR: PATHWAY TO SUSTAINABLE AGRICULTURE. - Abbas, Asiru (Innoriginal: International Journal of Sciences, 2018)
The study assessed postharvest losses which are like a recurring decimal in Nigerian agricultural sector, the driving factors and pro-active measures that can be adopted to tackle the problem. Nigeria’s population is increasing on annual basis and that is putting tremendous pressure on natural resources such as land, water, forest which means food wastage and loss must be avoided in order to avoid food insecurity especially in the face of unstable food prices and slow economic growth. Nigerian farmers are losing a lot in terms of monetary value occasioned by postharvest losses as many of them are plagued by inadequate storage facilities coupled with the fact that there are insufficient industries to add value to some of their farm produce and power supply is also erratic and this does not allow industries to operate at full capacity. The irony of the whole issue is that Nigeria is a country that produces crops such as cotton and cocoa but imports textile and chocolates from other countries of the world owing to inability to add value to some of her agricultural produce as local manufacturing ability is either very low or virtually non-existent in some areas. It is recommended that efficient and low cost technologies suited to the Nigerian environment should be developed to address the problem of postharvest losses through massive investment in agricultural research by the government, agro-allied industries etc. Farmers are also encouraged to form marketing cooperatives which will enable them to have a central location through which they can market their produce at reasonable prices and also link up with anchor buyers. Keywords: produce, storage, losses, postharvest, research, processing.